CYP1A2 genotype and acute effects of caffeine on resistance exercise, jumping, and sprinting performance. Issue 1 (15th April 2020) - Grgic, Jozo; Pickering, Craig; Bishop, David J.; Schoenfeld, Brad J.; Mikulic, Pavle; Pedisic, Zeljko
Abstract: Background: It has been suggested that polymorphisms within CYP1A2 impact inter-individual variation in the response to caffeine. The purpose of this study was to explore the acute effects of caffeine on resistance exercise, jumping, and sprinting performance in a sample of resistance-trained men, and to examine the influence of genetic variation of CYP1A2 (rs762551) on the individual variation in responses to caffeine ingestion. Methods: Twenty-two men were included as participants (AA homozygotes n = 13; C-allele carriers n = 9) and were tested after the ingestion of caffeine (3 mg/kg of body mass) and a placebo. Exercise performance was assessed with the following outcomes: (a) movement velocity and power output in the bench press exercise with loads of 25, 50, 75, and 90% of one-repetition maximum (1RM); (b) quality and quantity of performed repetitions in the bench press exercise performed to muscular failure with 85% 1RM; (c) vertical jump height in a countermovement jump test; and (d) power output in a Wingate test. Results: Compared to placebo, caffeine ingestion enhanced: (a) movement velocity and power output across all loads (effect size [ES]: 0.20–0.61; p < 0.05 for all); (b) the quality and quantity of performed repetitions with 85% of 1RM (ES: 0.27–0.85; p < 0.001 for all); (c) vertical jump height (ES: 0.15; p = 0.017); and (d) power output in the Wingate test (ES: 0.33–0.44; p < 0.05 for all). We did not find a significant genotype × caffeine interaction effect ( p -values ranged from 0.094 to 0.994) in any of the analyzed performance outcomes. Conclusions: Resistance-trained men may experience acute improvements in resistance exercise, jumping, and sprinting performance following the ingestion of caffeine. The comparisons of the effects of caffeine on exercise performance between individuals with the AA genotype and AC/CC genotypes found no significant differences. Trial registration: Australian New Zealand Clinical Trials Registry. ID: ACTRN12619000885190 .